Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Pada the Body Shop Botani Square Mall Bogor) - Laras Nur Aini; Nidaul Izzah (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine how much influence product quality and service quality have on consumer satisfaction (Study at The Body Shop of Botani Square Mall in Bogor). The research method used is quantitative methods. The sample consisted of 160 respondents who were selected using a non-probability sampling technique with the accidental sampling method. The data was analyzed by multiple linear regression analysis. The results showed that partially product quality has a significant influence on consumer satisfaction, with a value of 0.369 or 36.9%. Partially, service quality also has a significant effect on customer satisfaction, with a value of 0.176 or 17.6%. Simultaneously, product quality and service quality have a significant effect on customer satisfaction, with a value of 0.392 or 39.2%.